2021
DOI: 10.1029/2020gl091782
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Crustal P Wave Structure With Leaking Mode Dispersion Curves

Abstract: Rayleigh and Love wave dispersion curves are known as normal modes and are utilized for inversion. These two waves arrive after the S wave and account for the main energy in all waveforms. However, weaker signals arriving between the P and S waves also have dispersive properties, which are controlled by so-called leaking modes.Studies of leaking mode can be traced back to Somville (1930), who identified and named the PL phase. The PL phase is a train of long-period (>10 s) dispersed waveforms that arrive short… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…In the Z‐Z theoretical dispersion spectra calculated from the average inverted model, the energies of the Π modes and 1 st Σ mode that correspond to the dispersion of the PL phase are much stronger than those of the other Σ modes, which indicates that only the PL phase dispersion and guided modes can be extracted. Since, the controlling equation of the layered Vp structure dispersion is basically consistent with the controlling function of SH wave dispersion (Li, Shi et al., 2021), in this study, we believe that G1 can be reliably identified.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In the Z‐Z theoretical dispersion spectra calculated from the average inverted model, the energies of the Π modes and 1 st Σ mode that correspond to the dispersion of the PL phase are much stronger than those of the other Σ modes, which indicates that only the PL phase dispersion and guided modes can be extracted. Since, the controlling equation of the layered Vp structure dispersion is basically consistent with the controlling function of SH wave dispersion (Li, Shi et al., 2021), in this study, we believe that G1 can be reliably identified.…”
Section: Discussionsupporting
confidence: 77%
“…Figure 3f exhibits the summation of the absolute values of the sensitivity kernels of normal and leaking modes used in inversion (detailed sensitivity kernels are shown in Figure S5 in Supporting Information S1). Leaking modes exhibits a very complex sensitivity to Vs (which is similar to the sensitivity kernel of PL mode in Li, Shi et al, 2021), while its sensitivity kernels to Vp are similar to those of normal modes. Compared with the normal modes, the leaking modes penetrate to a deeper detection depth, as is also reflected in the convergence of the Vp models obtained from the inversions (Figure 3).…”
Section: Inversionmentioning
confidence: 87%
See 2 more Smart Citations
“…Subsequently, Li, Shi et al. (2021, 2022) verified the application of extracting normal mode and leaking mode dispersion curves by this method on earthquake records and ambient noise cross‐correlations. Currently, short‐period dense seismic arrays have been widely deployed for shallow structure imaging (Ma et al., 2020; Xie et al., 2021).…”
Section: Introductionmentioning
confidence: 99%